Performance of the Election Commission in Compiling the Final Voter List for the 2020 Regional Head Election - Rendy F. Sumigar; Stefanus Sampe; Donald Monintja (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Tadulako, 2022)
The goal of this research was to assess the Regional General Election Commission's (RGEC) effectiveness in creating the final voter list for the 2020 Regional Head Election. The East Bolaang Mongondow Regency RGEC was employed in this study. To determine the root reasons of the unsatisfactory Final Voter List preparation outcomes, researchers will assess the performance of the Boltim RGEC using three performance evaluation indicators identified by Agus Dwiyanto (2006:50), namely Productivity, Service Quality, and Accountability. The results showed that the performance of the East Bolaang Mongondow Regency General Election Commission in compiling the Final Voters List in the 2022 East Bolaang Mongondow Regional Head Election was ineffective because many residents who should have had the right to vote were not included in the Final Voters List because they were not recorded by the update officer. The East Bolaang Mongondow GEC's socialization of the phases of updating data has not been maximized, resulting in a lack of public understanding about updating voter data, voter data updating officers cannot adapt visits to the community whose data will be updated with community activities, there are voters who are not accommodated in the Register Permanent Voters even if they meet the requirements to be included in the Final Voters List, and finally, accountability is only carried out to certain parties, and the public is not aware of the accountability regarding the election use of the budget, particularly during the process of preparing the voter list.